World-wide contest of architecture elemental (2006)
The article displays the Colombian design proposal that obtained the MENTION OF HONOR in the “Worldwide contest of Architecture ELEMENTAL”. This consists in the construction of seven groups of houses of progressive development in Chile. The proposal also outlines the research frame that explain the actual situation of the Colombian inhabit sector. The research, in which the proposal has born, looks for to address the public action to the assistance of the socall “social production”. This last is the productive pattern in which the population of lower income solved its access to any form of lodging, that is to say in processes of progressive development, with the purpose of contribute to make of this practice a social and environmental sustainable one, and to obtain in this way a better habitat. The research also suggest that to integrate the strengths and potentialities of the social production in the construction of its lodging, with those of the state management, in order to produce an urban ground of quality, constitutes a management format that lays between us the way to give easibility to proposals like the one that is displayed in this article.